2020
DOI: 10.15407/dopovidi2020.03.047
|View full text |Cite
|
Sign up to set email alerts
|

The features of NiCx (x ⩽ 0.33) phase formation at the mechanochemical alloying of Ni-CNT and Ni-graphite mixtures

Abstract: В останні роки метод механохімічного синтезу (механічного легування), або обробки при кімнатній температурі вихідної шихти у високоенергетичному кульовому млині, успішно застосовувався нами для синтезу широкого класу подвійних карбідів і композиційних матеріалів на їх основі [1, 2]. Використання багатошарових вуглецевих нанотрубок (ВНТ) як вуглецевої компоненти шихти дало нам змогу синтезувати наноструктуровані карбіди d-перехідних металів TiC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Generally, the microhardness of the HT-HP sintered nickel carbide s likely to be affected by the crystal structure features. Thus, as we showed previously [21,22], the crystal structure of Ni3C carbide obtained from a Features of cubic Ni3C and NiC carbides obtained by HT-HP sintering towards the centers of its octahedral voids. These two types of characteristic arrangement of Carbon atoms in mechanically alloyed nickel carbide (Fig.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Generally, the microhardness of the HT-HP sintered nickel carbide s likely to be affected by the crystal structure features. Thus, as we showed previously [21,22], the crystal structure of Ni3C carbide obtained from a Features of cubic Ni3C and NiC carbides obtained by HT-HP sintering towards the centers of its octahedral voids. These two types of characteristic arrangement of Carbon atoms in mechanically alloyed nickel carbide (Fig.…”
Section: Resultssupporting
confidence: 65%
“…We have also shown that the existence region of this cubic nickel carbide expands at least to the NiC equiatomic composition, undergoing certain structural transformations [22,23].…”
Section: Features Of Cubic Ni3c and Nic Carbides Obtained By Ht-hp Si...mentioning
confidence: 72%
See 1 more Smart Citation